(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 1998)
The aim of this study is to compare how central modals are used in two subgenres of research articles: empirical and theoretical; and to provide a quantitative account of this usage. To achieve this objective, it investigates how the modals are distributed and what semantic and pragmatic functions they express within research articles in the journal Applied Linguistics. It also reviews how the research articles are constructed rhetorically and compares the distribution and the semantic and pragmatic functions of the central modals in each section of the two types of article.